The Influence of Organizational Culture and Work Disipline on Teachers Performance Through Work Motivation as An Intervening - Irma Nurhidayah; Christian Wiradendi Wolor; Agung Wahyu Handaru (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to determine the influence of organizational culture and work discipline on teacher performance with work motivation as a mediating variable, a case study of teachers in private high schools in Serang district. This study used a type of quantitative research that used a population of 590 teachers with a sample of 160 teachers in Serang district. Data collection techniques use questionnaires distributed online, and literature studies. Data analysis using Parcial Least Square (PLS) with SMARPLS 4.0 application. The results showed that organizational culture and work discipline had a direct positive and significant effect on the work motivation of private high school teachers. Then, organizational culture has a direct positive and significant effect on the performance of private high school teachers, while work discipline has a direct insignificant and negative effect on the performance of private high school teachers in Serang District, Banten. Work motivation has a positive and significant effect on the performance of private high school teachers in Serang District, Banten. Organizational culture and work discipline indirectly affect teacher performance through work motivation, which means that work motivation acts as an intervening variable.